2014
DOI: 10.3109/03639045.2014.884127
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin nanoemulsion for transdermal application: formulation and evaluation

Abstract: The aim of this work is to develop a curcumin nanoemulsion for transdermal delivery. The incorporation of curcumin inside a nanoglobul should improve curcumin stability and permeability. A nanoemulsion was prepared by the self-nanoemulsification method, using an oil phase of glyceryl monooleate, Cremophor RH40 and polyethylene glycol 400. Evaluation of the nanoemulsion included analysis of particle size, polydispersity index, zeta potential, physical stability, Raman spectrum and morphology. In addition, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 16 publications
7
80
0
7
Order By: Relevance
“…This also came in accordance with several other authors (Lucas-Abellán et al, 2007;Caddeo et al, 2008;Coimbra et al, 2011;Sessa et al, 2014), who declared that encapsulation of resveratrol in carriers, such as cyclodextrin complexes, liposomes and lecithin-based nanoemulsions were able to improve the stability of resveratrol. Similarly, this could be applied to curcumin, in which authors reported that its encapsulation in nanoformulations improves its stability (Rachmawati et al, 2015). The fact that the prepared nanoemulsion was able to maintain the concentration of the two polyphenols with no degradation, and preserve their antioxidant activity, proves that nanoemulsions provide an inert environment for both polyphenolic drugs.…”
Section: Stability Of the Selected Nanoemulsion Formulamentioning
confidence: 99%
“…This also came in accordance with several other authors (Lucas-Abellán et al, 2007;Caddeo et al, 2008;Coimbra et al, 2011;Sessa et al, 2014), who declared that encapsulation of resveratrol in carriers, such as cyclodextrin complexes, liposomes and lecithin-based nanoemulsions were able to improve the stability of resveratrol. Similarly, this could be applied to curcumin, in which authors reported that its encapsulation in nanoformulations improves its stability (Rachmawati et al, 2015). The fact that the prepared nanoemulsion was able to maintain the concentration of the two polyphenols with no degradation, and preserve their antioxidant activity, proves that nanoemulsions provide an inert environment for both polyphenolic drugs.…”
Section: Stability Of the Selected Nanoemulsion Formulamentioning
confidence: 99%
“…In the recent years, nanoemulsion has gain interest as a colloidal delivery system within the food, pharmaceuticals, cosmeceuticals, and other industries to encapsulate, protect and deliver bioactive lipophilic components, such as drugs, vitamins, neutraceuticals and antioxidants [5][6][7]. Nanoemulsion is defined as emulsion system having particle size ranging from 20 -500 nm [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, nanoemulsion can be prepared using two methods: the high energy method that involves the use of mechanical devices (e.g. ultrasonicator, rotor/stator system and high pressure homogenizer) and low energy method in which the chemical potential of the component is used such as phase inversion temperature (PIT), phase inversion composition (PIC) and spontaneous emulsification method [6][7]10].…”
Section: Introductionmentioning
confidence: 99%
“…166 Similarly curcumin nanoemulsions were developed using a self-nanoemulsifying method with the mean particle size of 85 nm and showed enhanced transdermal availability with high permeability and without degradation. 71 This might be useful in the skin care sectors for developing novel skin cream emulsions. In another study, lutein was successfully encapsulated into nanoemulsions in the size range of 150-350 nm and increased the release of the active compound compared to other lipid carriers.…”
Section: Nanosingle or Multiemulsionsmentioning
confidence: 99%
“…The aforementioned products prevent skin aging due to oxidative stress and premature aging. [69][70][71][72][73] The combination of polyphenols with retinols enhances skin protection. Other than nanosizing, few delivery systems have been used to develop nanoantiaging creams and lotions for the enhanced activity of bioactive compounds to deeper layers of skin.…”
Section: Phytoconstituent-based Nanocosmeceuticals For Skin Therapy Nmentioning
confidence: 99%